(untitled) - Huynh, Thi Trang (Melbourne, 2016)
This study examines library leadership and succession planning in Vietnam by investigating existing succession planning in Mekong Delta libraries; examing honw library leaders have dealt with succession planning challenges over the past decade; and positing a theoretical model for the succession planning process
Keywords: Kế hoạch nguồn nhân lực và hệ thống quản lý,Human Resources Planning and Management System